Effect of pH on rheotaxis of bull sperm using microfluidics. (16th May 2017) - El‐sherry, TM; Abdel‐Ghani, MA; Abou‐Khalil, NS; Elsayed, M; Abdelgawad, M
Contents: The aim of the present research is to study the effect of pH values on the sperm rheotaxis properties. Semen collected from bulls was diluted with SOF medium (1:10). pH of the medium was adjusted using a digital pH meter to the following pH values: 6.0, 6.2, 6.4, 6.4, 6.8, 7.0. All kinetic parameters of sperm ( n  = 3, 385) were determined through a computer‐assisted sperm analysis (CASA) system using microfluidic devices with controlled flow velocity. The following parameters were determined: total motility (TM%), positive rheotaxis (PR%), straightline velocity (VSL, μm/s), average path velocity (VAP, μm/s), linearity (LIN, as VSL/VCL, %), beat cross‐frequency (BCF, Hz) and curvilinear velocity (VCL, μm/s). Nitric oxide, calcium and potassium were estimated in semen at different pH values. To confirm the effect of nitric oxide and K +, we used sodium nitroprusside (an NO donor) and KCL as (a K + donor) to see their effect on sperm PR%. The results showed no difference in TM% at pH (6–7). The PR% was the lowest at pH 6 and 7. The best parameters for the PR% were at pH 6.4–6.6. The concentration of Ca +2 did not change at different pH values. The mean NO values decreased with the increase of pH; however, the mean values of K + increased with the increase of pH. Addition of high concentration of NO and K + to the semen media at fixed pH level had a negative effect on TM% and PR%. In conclusion, the bull sperm had the best rheotaxis properties at pH 6.4–6.6 and sensitive to the change of seminal NO and K + .